The Pacific century : America and Asia in a changing world - Gibney, Frank (New York : Charles Scribner's Sons, 1992)
"A Robert Stewart book."
Keywords: Pacific Area -- Relations -- United States..; East Asia -- History; United States -- Relations -- Pacific Area